2004
DOI: 10.1002/lsm.20070
|View full text |Cite
|
Sign up to set email alerts
|

The vascular response induced by transmyocardial laser revascularization is determined by the size of the channel scar: Results of CO2, holmium and excimer lasers

Abstract: These results indicate that the angiogenic response following TMLR is limited to the channel scar and related to the scar size rather than the specific laser type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Some studies have investigated endothelium‐lined patent channels 13–15. However, more experiments have shown that many laser channels are occluded by fibrous scar tissue after TMLR 16–18. Similarly, channels made by mechanical puncture can also become occluded 19…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated endothelium‐lined patent channels 13–15. However, more experiments have shown that many laser channels are occluded by fibrous scar tissue after TMLR 16–18. Similarly, channels made by mechanical puncture can also become occluded 19…”
Section: Discussionmentioning
confidence: 99%
“…With a smaller scar channel (CO 2 laser) there is greater angiogenesis in the scar. Additional experiments of histologically tracking laser tissue interactions over time revealed that the acute thermal injury and initial scarring at 2–3 weeks was greater with a Ho:YAG laser than with a CO 2 laser [13]. There was scar contracture over time and at 6 weeks there was little difference between the groups.…”
Section: Discussionmentioning
confidence: 99%